2012
DOI: 10.1103/physrevb.85.224436
|View full text |Cite
|
Sign up to set email alerts
|

Theory ofL-edge resonant inelastic x-ray scattering for magnetic excitations in two-leg spin ladders

Abstract: We study the magnetic excitation spectra of Cu L2,3-edge resonant inelastic x-ray scattering (RIXS) from the spin-liquid ground state in two-leg spin ladder cuprates. Applying the projection method developed by the present authors, we have derived the formulas of the magnetic RIXS spectra, which are expressed by one-and two-spin correlation functions in the polarization changing and preserving channels, respectively. The one-spin correlation function includes both one-and two-triplon excitations and they are p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…It was later shown that not only is this channel allowed but that it dominates the magnetic RIXS response in the undoped cuprates [31]. The RIXS spectra were later theoretically evaluated [8] employing a projection method for the two-leg ladder using the parameter set derived from La 4 Sr 10 Cu 24 O 41 in Ref. 23 (the model involved additional ring spin-exchange term as compared to our model).…”
Section: Revisiting Sr14cu24o41 Rixs Datamentioning
confidence: 99%
“…It was later shown that not only is this channel allowed but that it dominates the magnetic RIXS response in the undoped cuprates [31]. The RIXS spectra were later theoretically evaluated [8] employing a projection method for the two-leg ladder using the parameter set derived from La 4 Sr 10 Cu 24 O 41 in Ref. 23 (the model involved additional ring spin-exchange term as compared to our model).…”
Section: Revisiting Sr14cu24o41 Rixs Datamentioning
confidence: 99%
“…In undoped cuptares, using the Heisenberg model, the RIXS spectra arising from magnetic excitations have been calculated within the fast collision approximation 34,35 and with using a "projection" method to take account of the two-magnon excitations. [36][37][38] The present approximation scheme is unable to discuss such behavior in the strong coupling. To deal with the metallic phase with strong correlations, the present formalism for itinerant electron systems has to be extended by improving the HFA and the ladder approximation.…”
Section: Discussionmentioning
confidence: 84%
“…Although the spectra have been analyzed within the fast-collision approximation, 16,34,35 it could explain only the one-magnon contribution. The present authors have developed a "projection" method to go beyond the fast collision approximation, [36][37][38] and have explained quantitatively the spectral shape. These analyses are based on the localized spin model and utilize the 1/S expansion 39,40 to include the magnon-magnon interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we compare our two-dimensional dimerized Heisenberg system results to those of the quasi-1D spin ladder materials [43,44]. Experimentally Braicovich et.…”
Section: A K-edge Rixsmentioning
confidence: 99%
“…Resonant inelastic x-ray scattering can detect selection rule allowed triplon excitations with ∆S = 0, 1, 2, where ∆S refers to spin angular momentum change. In fact, experimental and theoretical RIXS efforts related to the study of triplon excitation for two-leg spin ladder have been reported in the literature [43][44][45]. The experimental study found two-triplon excitation signal in the spin ladder [33].…”
Section: Introductionmentioning
confidence: 99%